2009
DOI: 10.1103/physrevd.80.065017
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of the dimension-two gluon condensate: The zero temperature case

Abstract: We provide an algebraic study of the local composite operators A µ A ν − δ µν d A 2 κ and A 2 µ , with d = 4 the spacetime dimension. We prove that these are separately renormalizable to all orders in the Landau gauge. This corresponds to a renormalizable decomposition of the operator A µ A ν into its trace and traceless part. We present explicit results for the relevant renormalization group functions to three loop order, accompanied with various tests of these results. We then develop a formalism to determin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…This also implies that the electric-magnetic asymmetry observed [431,432] in dimension-two gluon condensates [433] at finite temperature is driven just by the electric sector [249]. Only the soft electric part is then left.…”
Section: Intermediate Momenta and Temperaturesmentioning
confidence: 88%
“…This also implies that the electric-magnetic asymmetry observed [431,432] in dimension-two gluon condensates [433] at finite temperature is driven just by the electric sector [249]. Only the soft electric part is then left.…”
Section: Intermediate Momenta and Temperaturesmentioning
confidence: 88%
“…This condensate then made its appearance in a variety of works, see e.g. [22,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. In the works [49,50], the relation was explored between this condensate and magnetic degrees of freedom, which are generally believed to play an important role for confinement.…”
Section: An Important Asset In the Computation D(pmentioning
confidence: 99%
“…In [18] the effective action in the presence of a dimension two condensate and of an asymmetry was computed. Since the starting point for the calculations when T 0 are identical, we shortly review the steps taken in [18].…”
Section: Preliminariesmentioning
confidence: 99%
“…In this paper we extend the computations in order to include finite temperature effects, with the aim of shedding more light on the results of [12]. In section II we give a short review of what was found in [18], which is then continued by a computation of the finite temperature effective action in section III. In section IV we find and discuss the minima of the potential, the values of the different condensates and their temperature dependence.…”
Section: Introductionmentioning
confidence: 99%